Ageing well with diabetes: A workshop to co‐design research recommendations for improving the diabetes care of older people. Issue 7 (4th February 2022) - Wylie, Thomas A. F.; Morris, Anna; Robertson, Elizabeth; Middleton, Ann; Newbert, Carolyn; Andersen, Birthe; Maltese, Giuseppe; Stocker, Rachel; Weightman, Andrew; Sinclair, Alan; Bain, Stephen C.
Abstract: Aims: To identify key research questions where answers could improve care for older people living with diabetes (PLWD), and provide detailed recommendations for researchers and research funders on how best to address them. Methods: A series of online research workshops were conducted, bringing together a range of PLWD and an acknowledged group of academic and clinical experts in their diabetes care to identify areas for future research. Throughout the pre‐workshop phase, during each workshop, and in manuscript preparation and editing, PLWD played an active and dynamic role in discussions as part of both an iterative and narrative process. Results: The following key questions in this field were identified, and research recommendations for each were developed: How can we improve our understanding of the characteristics of older people living with diabetes (PLWD) and their outcomes, and can this deliver better person‐centred care? How are services to care for older PLWD currently delivered, both for their diabetes and other conditions? How can we optimise and streamline the process and ensure everyone gets the best care, tailored to their individual needs? What tools might be used to evaluate the level of understanding of diabetes in the older population amongst non‐specialist Healthcare Professionals (HCPs)? How can virtual experts or centres most effectively provide access to specialist multi‐disciplinary team (MDT) expertise for older PLWD and the HCPs caring for them? Is a combination of exercise and a nutrition‐dense, high protein diet effective in the prevention of the adverse effects of type 2 diabetes and deterioration in frailty, and how might this be delivered in a way which is acceptable to people with type 2 diabetes? How might we best use continuous glucose monitoring (CGM) in older people and, for those who require support, how should the data be shared? How can older PLWD be better empowered to manage their diabetes in their own home, particularly when living with additional long‐term conditions? What are the benefits of models of peer support for older PLWD, both when living independently and when in care? Conclusions: This paper outlines recommendations supported by PLWD through which new research could improve their diabetes care and calls on the research community and funders to address them in future research programmes and strategies.